Dendrobium mixture ameliorates type 2 diabetes mellitus with non-alcoholic fatty liver disease through PPAR gamma: An integrated study of bioinformatics analysis and experimental verification - Zhuang, Shuting; Zhang, Jieping; Lin, Xiaohui; Wang, Xiaoning; Yu, Wenzhen; Shi, Hong (Frontiers in Pharmacology, 2023)
Dendrobium mixture (DM) is a patented Chinese herbal medicine indicated which has anti-inflammatory and improved glycolipid metabolism. However, its active ingredients, targets of action, and potential mechanisms are still uncertain. Here, we investigate the role of DM as a prospective modulator of protection against nonalcoholic fatty liver disease (NAFLD) induced by type 2 diabetes mellitus (T2DM) and illustrate the molecular mechanisms potentially involved. The network pharmacology and TMT-based quantitative protomics analysis were conducted to identify potential gene targets of the active ingredients in DM against NAFLD and T2DM. DM was administered to the mice of DM group for 4 weeks, and db/m mice (control group) and db/db mice (model group) were gavaged by normal saline. DM was also given to Sprague-Dawley (SD) rats, and the serum was subjected to the palmitic acid-induced HepG2 cells with abnormal lipid metabolism. The mechanism of DM protection against T2DM-NAFLD is to improve liver function and pathological morphology by promoting peroxisome proliferator-activated receptor γ (PPARγ) activation, lowering blood glucose, improving insulin resistance (IR), and reducing inflammatory factors. In db/db mice, DM reduced RBG, body weight, and serum lipids levels, and significantly alleviated histological damage of liver steatosis and inflammation. It upregulated the PPARγ corresponding to the prediction from the bioinformatics analysis. DM significantly reduced inflammation by activating PPARγ in both db/db mice and palmitic acid-induced HepG2 cells.